1999
DOI: 10.1016/s0886-3350(99)00143-1
|View full text |Cite
|
Sign up to set email alerts
|

Scleral perforation during retrobulbar and peribulbar anesthesia: risk factors and outcome in 50 000 consecutive injections

Abstract: Eyes with posterior staphyloma sustained needlestick injuries at a rate of 1 in 760 compared with 0 injection perforations in more than 44,000 nonstaphylomatous eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 32 publications
2
43
1
Order By: Relevance
“…He was able to subcategorize block-induced periocular bleeding into three groups: (1) minor hemorrhage caused by damage to a vein or small artery that produces a palpable elevation in intraocular pressure (IOP); (2) arterial hemorrhage producing rapid proptosis and raised IOP; and (3) concealed hemorrhage in which blood remains within the muscular cone and produces elevations in IOP without visible evidence of orbital hemorrhage. In a review of 50,000 eye blocks, Edge and Navon [5] found that myopia is only a significant risk factor for inadvertent perforation when associated with staphyloma.…”
Section: Retrobulbar Anaesthesiamentioning
confidence: 99%
“…He was able to subcategorize block-induced periocular bleeding into three groups: (1) minor hemorrhage caused by damage to a vein or small artery that produces a palpable elevation in intraocular pressure (IOP); (2) arterial hemorrhage producing rapid proptosis and raised IOP; and (3) concealed hemorrhage in which blood remains within the muscular cone and produces elevations in IOP without visible evidence of orbital hemorrhage. In a review of 50,000 eye blocks, Edge and Navon [5] found that myopia is only a significant risk factor for inadvertent perforation when associated with staphyloma.…”
Section: Retrobulbar Anaesthesiamentioning
confidence: 99%
“…The incidence is between 1 of 350 and 7 of 50,000 cases. 29,30 Main risk factors include inadequate experience of the physician and a highly myopic eye (ie, long eyeball). 30 In a 50,000 case experience, Edge and Navon 29 observed that myopic staphyloma was the greater risk factor.…”
Section: Figmentioning
confidence: 99%
“…Previous studies have suggested the following risk factors for globe perforation: posterior staphyloma, 8 long axial length 9 and inexperienced personnel. 10 None of the patients presented here had posterior staphyloma and only Case 1 had an axial length at the upper end of the normal range at 25.5 mm.…”
Section: Commentmentioning
confidence: 99%
“…Although the exact mechanism of action remains uncertain, it is likely that absorption of the contained sympathomimetic agents through the nasal mucosa (as has been reported for cocaine 7,8 ), aggravated by the patient sitting in a darkened room to relieve his photophobia, was the trigger factor in an, albeit low, hypermetropic patient to produce bilateral AACG. We would suggest that the packaging of such products should alert patients (and their doctors) to this risk.…”
mentioning
confidence: 99%